Considering Interinstitutional Visibilities in Combating Misinformation. Issue 5 (14th June 2022) - Bélair-Gagnon, Valérie; Graves, Lucas; Kalsnes, Bente; Steensen, Steen; Westlund, Oscar
Abstract: This introduction to the special issue "Fighting Fakes: News publishers, fact-checkers, platform companies, and policymaking" argues that the institutionalization of interactions related to misinformation is central to scholarly understandings of the visibility and structural inequalities of institutionalized efforts to fighting fakes . We look at the ways that contributors of this special issue have shown how materialities, institutions, practices, politics, economics, and culture shape the field of fighting fakes .